Esophageal positions relative to the left atrium; data from 293 patients before catheter ablation of atrial fibrillation - Starek, Zdenek; Lehar, Frantisek; Jez, Jiri; Scurek, Martin; Wolf, Jiri; Kulik, Tomas; Zbankova, Alena (Indian heart journal, 2018)
AIMS: Three-dimensional rotational angiography (3DRA) of the left atrium (LA) and the esophagus is a simple and safe method for analyzing the relationship between the esophagus and the LA during catheter ablation of atrial fibrillation. The purpose of this study is to describe the location of the esophagus relative to the LA and mobility of the esophagus during ablation procedure. METHODS: From 3/2011 to 9/2015, 3DRA of the LA and esophagus was performed in 326 patients before catheter ablation of atrial fibrillation. 3DRAwas performed with visualization of the esophagus via peroral administration of a contrast agent. The positions of the esophagus were determined at the beginning of the procedure, for part of patients also at the end of procedure with contrast esophagography. RESULTS: The most frequent position is behind the center of the LA (91 pts., 31.9%) The least frequent position is behind the right pulmonary veins (27 pts., 9.4%). The average shift of the esophagus position was 3.36±2.15mm, 3.59±2.37mm and 3.67±3.23mm for superior, middle and inferior segment resp. CONCLUSIONS: The position of the esophagus to the LA is highly variable. The most common position of the esophagus relative to the LA is behind the middle and left part of the posterior wall of the LA. The least frequently observed position is behind the right pulmonary veins. No significant position change of esophagus motion from before to after the ablation procedure in the majority (≥95%) of the patients was observed.
Keywords: Reproducibility of Results; chirurgie s pomocí počítače; Fluoroscopy; 3D rotational angiography of the left atrium and esophagus; Catheter ablation of atrial fibrillation; reprodukovatelnost výsledků; Heart Atria; Retrospective Studies; katetrizační ablace; Atrioesophageal fistula; Middle Aged; mužské pohlaví; Esophagus; fluoroskopie; srdeční síně; převodní systém srdeční; Catheter Ablation; ženské pohlaví; Position of esophagus to the left atrium; retrospektivní studie; Humans; CT angiografie; Shortterm mobility of the esophagus; Heart Conduction System; zobrazování trojrozměrné; fibrilace síní; lidé středního věku; Computed Tomography Angiography; Imaging, Three-Dimensional; Image integration; Female; Surgery, Computer-Assisted; Atrial Fibrillation; ezofágus; lidé; Male